Каталiз обриву ланцюгiв окиснення 1,3-циклогексадiєну бiс(N-фенiлантранiлатами) неперехiдних металiв - Суховєєв, О.В.; Ковтун, Г.О.; Суховєєв, В.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The catalysis of oxidization chain termination of 1,3-cyclohexadiene by bis(N-phenylanthranilates) of nontransition metals ML2 (Mg, Ca, Sr, Ba) at 50 ◦ C is determined. The mechanism of catalysis which is realized in the alternated reactions of hydroperoxide radicals HOO with > NH− and > N. -groups of a co-ordinated ligand is grounded:
HOO. + > NH -> N . +H2O2
HOO. + > N . -> O2+ > NH.
The rate constants of the interaction of radicals HOO with ML2 are measured: 10−4 . k= 4.6 ± 0.3 (Ba), (2.1 ± 0.2) (Ca), (1.0 ± 0.2) (Sr), (0.6 ± 0.1) l/(mol + s) (Mg) at 50 ◦ С.